Effect of apatinib plus neoadjuvant chemotherapy followed by resection on pathologic response in patients with locally advanced gastric adenocarcinoma: A single-arm, open-label, phase II trial. (May 2020) - Zheng, Yanan; Yang, Xiao; Yan, Chao; Feng, Runhua; Sah, Birendra Kumar; Yang, Zhongyin; Zhu, Zhenglun; Liu, Wentao; Xu, Wei; Ni, Zhentian; Beeharry, Maneesh Kumarsing; Hua, Zichen; et al.
Abstract: Background: The evidence of combining neoadjuvant chemotherapy with targeted therapy for patients with locally advanced gastric cancer is inadequate. We conducted a single-arm phase II trial to evaluate the efficacy and safety of S-1, oxaliplatin and apatinib (SOXA) in patients with locally advanced gastric adenocarcinoma. Methods: Treatment-naïve patients received three preoperative cycles of S-1 (80–120 mg/day on days 1–14) and oxaliplatin (130 mg/m 2 on day 1) and two cycles of apatinib (500 mg/day for 21 days) at 3-week intervals, followed by surgery. The primary end-point was pathologic response rate (pRR). This trial is registered at ChiCTR.gov.cn: ChiCTR-OPC-16010061. Results: Of 29 patients included, median age was 60 (range, 43–73) years; 20 (69.0%) were male. The pRR was 89.7% (95% confidence interval [CI], 72.7%–97.8%; 26 of 29 patients; P < 0.001) with 28 patients treated with surgery. All 29 patients were available for preoperative response evaluation, achieving an objective response rate of 79.3% (95% CI, 60.3%–92.0%) and a disease control rate of 96.6% (95% CI, 82.2%–99.9%). The margin-free resection rate was 96.6% (95% CI, 82.2%–99.9%). The pathologic complete response rate was 13.8% (95%CI, 1.2%–26.3%). Downstaging of overall TNM stage was observed in 16 (55.2%) patients. During neoadjuvant therapy, 10 (34.5%) patients had grade ≥III adverse events. No treatment-related death occurred. Surgery-related complications were observed in 12 of 28 (42.9%) patients. Conclusion: SOXA followed by surgery in patients with locally advanced gastric adenocarcinoma showed favourable activity and manageable safety. A randomised controlled trial in locally advanced gastric or oesophagogastric junction adenocarcinoma is ongoing (ClinicalTrials.gov: NCT04208347 ). Highlights: Treatment-naïve patients received S-1, oxaliplatin and apatinib before surgery. Pathologic response rate was used as a primary end-point. The pathologic response rate was 89.7%, with acceptable safety. The pathologic complete response rate was 13.8%. Neoadjuvant chemotherapy + apatinib was feasible for locally advanced gastric cancer.